In which patients the best efficacy of secukinumab? Update of a real-life analysis after 136 weeks of treatment with secukinumab in moderate-to-severe plaque psoriasis. (1st February 2020) - Galluzzo, Marco; D'Adamio, Simone; Silvaggio, Dionisio; Lombardo, Paolo; Bianchi, Luca; Talamonti, Marina
ABSTRACT: Background : There is limited long-term, real-world evidence on the efficacy and safety in patients with plaque psoriasis treated with secukinumab. We present results at 136 weeks in a real-world setting with focus on special populations. Research design and methods : Retrospective analysis of 151 patients with chronic plaque psoriasis who initiated treatment with secukinumab between September 2015 and May 2019. Secukinumab 300 mg was administered once weekly for 5 weeks followed by once monthly. Main outcome measures : Clinical and laboratory assessments were performed up to 136 weeks. Results : At 16 weeks, 90%, 79%, and 63% of patients achieved Psoriasis Area and Severity Index (PASI) 75, PASI 90, and PASI 100, respectively, compared with 79%, 72%, and 55% of patients after 136 weeks of therapy with secukinumab. Fifteen of the 151 patients experienced an adverse event, the most common of which was candida infection (4%). Biological treatment naïve was significantly associated with response to therapy at 1 and 2 years (P < 0.0001). There were no safety issues in patients with infection with HBV, HCV or mycobacterium tuberculosis. Conclusions : Our results confirm the rapidity of action of secukinumab as well as its long-lasting efficacy and good safety in real-world clinical practice.